Vertebral Artery Erosion into Cervical Vertebral Body and ACDF Complications: Case Report and Review of Literature. (16th November 2020) - Abu-Rmaileh, Muhammad; Afuwape, Olusoji A; Helton, Matthew; Stephens, Marcus L; Walters, Jerry L; Kazemi, Noojan
Abstract: INTRODUCTION: A tortuous course of the vertebral artery (VA) is a well-known anatomic variant, with an incidence of 2.7 - 7.6%. Of the 4 types of classified vertebral artery anatomic variations, Type 4 defines migration into the vertebral body medial to the vertical plane. Risk of vertebral artery injury is significantly higher in patients undergoing anterior cervical spine surgery harboring a highly tortuous vertebral artery. While the literature review for vertebral artery injury is between 0.08%-1.4% the true injury rate of vertebral artery injury in anterior cervical spine surgery has not been well documented. METHODS: We performed a comprehensive medical literature search including Medline, Embase and systematic review databases for vertebral artery complications for anterior cervical spine surgery (ACS) including discectomy and fusion. We added an observed case of tortuous vertebral artery with erosion into the C4 vertebral body with surgical management. RESULTS: 10 retrospective case series were identified reporting VA injury during anterior cervical surgery. These included 29 injuries during 9187 ACS surgeries (0.32%) and ranged from 0.13% to 0.95% incidence rate amongst the series. None described the type 4 variant. Our case represented a type 4 VA anatomic variant that was identified on close observation on MRI together with follow up CTA imaging. Surgical options including modifying the operative approach as well as potential microvascular transposition of the VA where indicated. CONCLUSION: VA injury is an uncommon but significant risk during anterior cervical spine surgery. Close observation of and appropriate selection of preoperative imaging can potentially avoid vertebral artery injury including the least common (and most frightening) type 4 vertebral artery anatomic variant.